A robot leg for biped walking - Cabancla, Lloyd M. (2004)
This paper presents the design of a robot leg for use in biped walking. The primary motivation of this work is to create a platform for bipedal walking research. The robot's design uses affordable off-the-shelf components. The robot leg has five degrees of freedom, which are powered using DC motors. The mechanical structure of the leg is similar to that of a human leg. It is 50 centimeters tall and weighs 2 kilograms.